How are undergraduate STEM instructors leveraging student thinking? - Jessica Gehrtz; Molly Brantner; Tessa C. Andrews (SpringerOpen, 2022)
Abstract Background STEM instructors who leverage student thinking can positively influence student outcomes and build their own teaching expertise. Leveraging student thinking involves using the substance of student thinking to inform instruction. The ways in which instructors leverage student thinking in undergraduate STEM contexts, and what enables them to do so effectively, remains largely unexplored. We investigated how undergraduate STEM faculty leverage student thinking in their teaching, focusing on faculty who engage students in work during class. Results From analyzing interviews and video of a class lesson for eight undergraduate STEM instructors, we identified a group of instructors who exhibited high levels of leveraging student thinking (high-leveragers) and a group of instructors who exhibited low levels of leveraging student thinking (low-leveragers). High-leveragers behaved as if student thinking was central to their instruction. We saw this in how they accessed student thinking, worked to interpret it, and responded in the moment and after class. High-leveragers spent about twice as much class time getting access to detailed information about student thinking compared to low-leveragers. High-leveragers then altered instructional plans from lesson to lesson and during a lesson based on their interpretation of student thinking. Critically, high-leveragers also drew on much more extensive knowledge of student thinking, a component of pedagogical content knowledge, than did low-leveragers. High-leveragers used knowledge of student thinking to create access to more substantive student thinking, shape real-time interpretations, and inform how and when to respond. In contrast, low-leveragers accessed student thinking less frequently, interpreted student thinking superficially or not at all, and never discussed adjusting the content or problems for the following lesson. Conclusions This study revealed that not all undergraduate STEM instructors who actively engage students in work during class are also leveraging student thinking. In other words, not all student-centered instruction is student-thinking-centered instruction. We discuss possible explanations for why some STEM instructors are leveraging student thinking and others are not. In order to realize the benefits of student-centered instruction for undergraduates, we may need to support undergraduate STEM instructors in learning how to learn from their teaching experiences by leveraging student thinking.